2015
DOI: 10.3109/13880209.2015.1034326
|View full text |Cite
|
Sign up to set email alerts
|

Identification of natural products as modulators of OATP2B1 using LC-MS/MS to quantify OATP-mediated uptake

Abstract: Context: Organic anion-transporting polypeptide 2B1 (OATP2B1) which is highly expressed in enterocytes and hepatocytes could be a key determinant for the intestinal absorption and hepatic uptake of its substrate drugs. Natural products are commonly used in traditional Chinese medicine, foods, and beverages. Objective: The objective of this study is to determine the OATP2B1-mediated drug interactions that could occur between natural products and OATP2B1 substrate drugs. Materials and methods: Human OATP2B1 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…Additionally, some constituents that are not listed in these tables such as (-)-catechin, chlorogenic acid, (-)-epicatechin, (-)-epigallocatechin, (-)-epigallocatechin gallate, kaempferol, naringenin, and phlorhizin showed moderate-to-weak inhibition of these transporters. 30,32,96,192,[194][195][196] Taken together, these in vitro findings confirm the ability of these natural products to inhibit intestinal OATPs. Indeed, among the 9 inhibitors identified in the clinical DDI studies (Table 4), apple juice, grapefruit juice, green tea, and orange juice all exhibited potent inhibition in vivo, reducing the exposure of co-administered victim drugs by up to 85%.…”
Section: In Vitro Inhibitors Of Oatp2b1 and Oatp1a2supporting
confidence: 68%
“…Additionally, some constituents that are not listed in these tables such as (-)-catechin, chlorogenic acid, (-)-epicatechin, (-)-epigallocatechin, (-)-epigallocatechin gallate, kaempferol, naringenin, and phlorhizin showed moderate-to-weak inhibition of these transporters. 30,32,96,192,[194][195][196] Taken together, these in vitro findings confirm the ability of these natural products to inhibit intestinal OATPs. Indeed, among the 9 inhibitors identified in the clinical DDI studies (Table 4), apple juice, grapefruit juice, green tea, and orange juice all exhibited potent inhibition in vivo, reducing the exposure of co-administered victim drugs by up to 85%.…”
Section: In Vitro Inhibitors Of Oatp2b1 and Oatp1a2supporting
confidence: 68%
“…For example, the antifungal ketoconazole, a potent inhibitor of CYP3A4, causes drug-drug interactions with drugs that are substrates of CYP3A4 (Xiaoyang et al 2015). However, undesired drug-drug interactions can also be caused by transporters (Kim et al 1998;Li et al 2014;Joyce et al 2015;Wen et al 2016). Some drug interactions, previously believed to be P450-mediated, are now considered at least in part due to the inhibition of transport proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The flavonoid scutellarin is enriched in breviscapine. Extracts from these natural sources have been found to impair the transport function of OATPs in the over-expressing cells [ 67 , 72 , 76 ]. Horny Goat Weed is a widely used Chinese medicine in Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, licorice contains the saponin glycyrrhizic acid, which has been in managing chronic hepatitis and gastric ulcers. Glycyrrhizic acid was reported to inhibit the cellular uptake of OATP substrates atorvastatin, fluvastatin and rosuvastatin [ 76 ]. Literature also indicated that chemically similar molecules like the triterpenoid saponins ursolic acid, oleanolic acid and betulinic acid, are potent OATP inhibitors [ 64 , 68 ].…”
Section: Introductionmentioning
confidence: 99%